Ileal cystic lymphangioma presenting with acute appendicitis - Su-Ann Lui; Yoke Lin Nyo; V P Mali (Wolters Kluwer Medknow Publications, 2018)
Mesenteric lymphatic malformations are rare benign tumors that are most commonly found in children. The presentation of these tumors can be variable. It has been suggested that mesenteric lymphatic malformations are congenital; however, there is evidence that their size may be increased by infection. A 3-year 10-month-old boy presented with rhinorrhea and cough followed by acute abdominal pain. Ultrasonography revealed a lobulated mass in the lower abdomen. Computerized tomography scan of the abdomen diagnosed an inflamed appendix with perforation. Laparotomy revealed a multicystic mass within the mesentery closely adherent to the ileum; with omentum wrapped around. The appendix was dilated and firm. An ileal resection and an appendicectomy were performed. Histology confirmed acute transmural appendicitis with concurrent cystic lymphangioma of the ileal mesentery. Although rare, cystic lymphangioma must be considered in the differential of pediatric acute abdomen. Surgeons must be aware of this association and be reminded to inspect the rest of small bowel during appendicectomy especially if the preoperative imaging is suspicious.